2005
DOI: 10.1002/ana.20405
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, sex, and risk for Alzheimer's disease

Abstract: Depression associates with increased risk for dementia and Alzheimer's disease (AD), although it is unclear whether it represents an actual risk factor or a prodrome. To determine the relative hazard of premorbid depressive symptomatology for development of dementia and AD, we studied risk for incident dementia and AD over a 14-year period in 1,357 community-dwelling men and women participating in the 40-year prospective Baltimore Longitudinal Study of Aging. Screening for depressive symptoms, comprehensive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
3
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 72 publications
10
138
3
4
Order By: Relevance
“…25 Similarly, other studies have found that men appear to be more vulnerable to the adverse impacts of depressive syndromes on cognitive functioning and brain integrity. 33,34 We did not find such a sex difference in the present study.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofmentioning
confidence: 90%
See 1 more Smart Citation
“…25 Similarly, other studies have found that men appear to be more vulnerable to the adverse impacts of depressive syndromes on cognitive functioning and brain integrity. 33,34 We did not find such a sex difference in the present study.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofmentioning
confidence: 90%
“…These results are consistent with previous studies which have reported a relationship between a history of depression or DS and risk for cognitive impairment and dementia. 4,5,7,24,25 Most previous studies have relied on dichotomous depression groups or continuous measures of DS at 1 time point. A dosedependent relationship between severe depressive episodes and dementia risk was found in a study that reported an average 13% increase in the risk of dementia with every episode leading to hospitalization for depression.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofmentioning
confidence: 99%
“…Although the relationship among soluble Ab, brain neurochemistry and depression remains complex, several studies have demonstrated an increased risk for the development of AD in individuals with late-life depression, suggesting a prodromal state of AD (Steffens et al, 1997;Dal Forno et al, 2005;Sun et al, 2008). Ab may have an effect on mood not limited to non AD patients, depression-like symptoms may indeed precede or accompany dementia (Starkstein et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a recent meta-analysis (Hajek et al 2011) support this theory as they reported that even in healthy carriers of the BDNF Val66Met polymorphism hippocampal volume was reduced compared to Val/Val homozygotes, although the effect sizes in the individual studies were so small, that only the meta-analysis could show the actual difference, supposedly because participants with smaller hippocampal volumes were already excluded for being depressed. Older participants are also more likely to suffer from late-onset depression, which has been suggested to often precede the onset of demen-tia, especially Alzheimer's disease (Saczynski et al 2010;Dal Forno et al 2005), which is also associated with a more pronounced hippocampal degeneration (Laakso et al 1998;Ryu et al 2010). BDNF Val66Met polymorphism has been previously associated with depressive symptoms in patients with Alzheimer's disease (Borroni et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, altered neutrophin production might result in a decreased ability for neuronal repair and plasticity. Older participants are also more likely to suffer from late-onset depression, which often precedes the onset of dementia, especially Alzheimer's disease (Saczynski et al 2010;Dal Forno et al 2005). Alzheimer's disease is also associated with substantial hippocampal degeneration (Laakso et al 1998;Ryu et al 2010), and BDNF polymorphisms (rs6265 and rs7124442) have also been examined in relation to it (Borroni et al 2009;Huang et al 2007).…”
Section: Introductionmentioning
confidence: 99%